Scheuthauer-Marie-Sainton syndrome: a case report - Ramalingam, Shakila; Saravanan, Thalaimalai; Raghupathy, L. P.; Jaisankar, Sowmiya (International Journal of Research in Medical Sciences, 2022)
The term Scheuthauer-Marie-Sainton syndrome is also known as cleidocranial dysplasia or cleidocranial dystosis and is derived from ancient greek words cleido (collar bone), knanion (head) and dysplasia (abnormal formation). It is an uncommon but well known genetic skeletal condition and an autosomal dominant malformation affecting bones and teeth. The most common skeletal and dental abnormalities in affected individuals are hypoplastic/ aplastic clavicles, open frontanelles, short stature, retention of primary teeth, delayed eruption of permanent teeth, supernumerary teeth and multiple impacted teeth. Affected person have a characteristic facial appearance with a bulky forehead, hypertelorism and midfacial hypoplasia. General health is usually good and the intellect is unimpaired. This article describes clinical and radiographic features of Scheuthauer-Marie-Sainton syndrome in a 29 years old male patient